Chart shewing the track of the Sledge James Fitzjames from March 10th to April 19th 1853 also of the Sledge John Dyer between May 5th and June 9th 1853 forming a part of the searching operations from H. M. S. Resolute, Capt. H. Kellett, C.B., both Sledges under charge of William T. Domville M.D., Surgeon / Day & Son Lithrs. to the Queen (Hydrographic Office of the Admiralty, 1855)
Recd. H.O. 30th Septr. 1854 D.1002. Color;